POLYSEMY IN COGNITIVE LINGUISTICS - Dalieva Madina (Web of Journals Publishing, 2024)
This article introduces the field of polysemy and synonymy studies from a Cognitive Linguistic perspective. Firstly, the discussion explains and defines the object of research, showing that the study of semantic relations, traditionally restricted to the description of lexical semantics, needs to be extended to include all formal structures, including morpho-syntax. Secondly, given the theoretical assumptions of Cognitive Linguistics, it is argued that quantitative corpus-driven methods are essential for the description of semantic structures.
Keywords: Cognitive Linguistics, corpus linguistics, polysemy, prototype semantics, quantification, radial network analysis.